DETERMINAN KEJADIAN KELELAHAN KERJA PADA PERAWAT DAN BIDAN DI INSTALASI RAWAT INAP RSUD SOLOK SELATAN TAHUN 2023 - Apriliani, Cici; Suwito, Adriani; Berliani, Hamida; Akbar, Fauzan; Alhamda, Syukra (HUMAN CARE JOURNAL, 2024)
The World Health Organization (WHO) predicts that the second leading killer after heart disease is severe fatigue. According to the Workers' Social Security Agency (BPJS Ketenagakerjaan) in West Sumatra, in 2021, there were 31,801 reported cases of occupational accidents, representing a 16.96% increase from the previous year. The purpose of this study is to determine the factors influencing fatigue among nurses and midwives in the Inpatient Department of Solok Selatan Regional Hospital. This research is an analytical survey with a cross-sectional approach. The total sampling method was used to select 84 respondents. Data processing was computerized, and the results were presented in the form of frequency distribution tables. The research findings revealed that work fatigue was at 59.5%, heavy workloads at 60.7%, unsafe working conditions at 56%, severe job-related stress at 53.6%, and long working tenure at 56%. Statistical analysis concluded that there is a significant relationship between workload (α = 0.05 with OR = 2.625), working conditions (α = 0.003 with OR = 4.278), job-related stress (α = 0.001 with OR = 5.600), and work tenure (α = 0.013 with OR = 3.433) and work fatigue. In summary, workload, working conditions, job-related stress, and work tenure are significantly associated with work fatigue. To address work fatigue, nurses and midwives are encouraged to manage job-related stress effectively, support each other to reduce workloads, and engage in team-building activities such as outbound events to strengthen teamwork.